Identification and characterization of a matrix protein (PPP‐10) in the periostracum of the pearl oyster, Pinctada fucata. Issue 1 (7th October 2013) - Nakayama, Seiji; Suzuki, Michio; Endo, Hirotoshi; Iimura, Kurin; Kinoshita, Shigeharu; Watabe, Shugo; Kogure, Toshihiro; Nagasawa, Hiromichi
Abstract : The periostracum is a layered structure that is formed as a mollusk shell grows. The shell is covered by the periostracum, which consists of organic matrices that prevent decalcification of the shell. In the present study, we discovered the presence of chitin in the periostracum and identified a novel matrix protein, Pinctada fucata periostracum protein named PPP‐10. It was purified from the sodium dodecyl sulfate/dithiothreitol‐soluble fraction of the periostracum of the Japanese pearl oyster, P. fucata . The deduced amino acid sequence was determined by a combination of amino acid sequence analysis and cDNA cloning. The open reading frame encoded a precursor protein of 112 amino acid residues including a 21‐residue signal peptide. The 91 residues following the signal peptide contained abundant Cys and Tyr residues. PPP‐10 was expressed on the outer side of the outer fold in the mantle, indicating that PPP‐10 was present in the second or third layer of the periostracum. We also determined that the recombinant PPP‐10 had chitin‐binding activity and could incorporate chitin into the scaffolds of the periostracum. These results shed light on the early steps in mollusk shell formation. Abstract : The periostracum is a layered structure that is formed as a mollusk shell grows. The organic framework of the periostracum probably contains chitin. The protein PPP‐10 was identified from the periostracum of Pinctada fucata . PPP‐10 is a chitin‐binding protein that is expressed at the mantle edge.